Symmetric and Anti-Symmetric Solitons of the Fractional Second- and Third-Order Nonlinear Schrödinger Equation - Cao, Qi-Hao; Dai, Chao-Qing (Chinese physics letters, 2021)
The fractional second-and third-order nonlinear Schr?dinger equation is studied,symmetric and antisymmetric soliton solutions are derived,and the influence of the Levy index on different solitons is analyzed.The stability and stability interval of solitons are discussed.The anti-interference ability of stable solitons to the small disturbance shows a good robustness.